2003
DOI: 10.1095/biolreprod.102.014076
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Regulation of DNA Methyltransferase Expression in Cloned Mouse Embryos1

Abstract: Cloning by somatic cell nuclear transfer is inefficient. This is evident in the significant attrition in the number of surviving cloned offspring at virtually all stages of embryonic and fetal development. We find that cloned preimplantation mouse embryos aberrantly express the somatic form of the Dnmt1 DNA (cytosine-5) methyltransferase, the expression of which is normally prevented by a posttranscriptional mechanism. Additionally, the maternal oocyte-derived Dnmt1o isoform undergoes little or none of its exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 27 publications
5
74
0
1
Order By: Relevance
“…Based on the reports that most NT embryos cease development at the pre-and peri-implantation stages [1,41], it is probable that the accumulation of different abnormalities observed in NT embryos at various developmental stages, such as failure to erase some of the features of donor cells [42][43][44], abnormal gene expression [4,8,10,25,[45][46][47], abnormal DNA methylation [4][5][6], abnormal formation of placentae [1,41,[48][49][50], and the abnormalities detected in this study, leads to gradual loss of NT embryos. Abnormalities that have not been detected in previous studies and/or small differences in gene expression may seriously affect embryonic development.…”
Section: Discussionmentioning
confidence: 72%
“…Based on the reports that most NT embryos cease development at the pre-and peri-implantation stages [1,41], it is probable that the accumulation of different abnormalities observed in NT embryos at various developmental stages, such as failure to erase some of the features of donor cells [42][43][44], abnormal gene expression [4,8,10,25,[45][46][47], abnormal DNA methylation [4][5][6], abnormal formation of placentae [1,41,[48][49][50], and the abnormalities detected in this study, leads to gradual loss of NT embryos. Abnormalities that have not been detected in previous studies and/or small differences in gene expression may seriously affect embryonic development.…”
Section: Discussionmentioning
confidence: 72%
“…Kwon et al [46] also found global hypermethylated DNA at the 4-cell stage of porcine SCNT embryos compared with IVF embryos using a 5-methylcytosine (5-MeC) antibody immunostaining method. An abnormally increased expression of Dnmt1 protein has also been observed in the 8-cell stage cloned murine embryos reconstructed from cumulus cells [47]. These abnormal levels of embryonic methylation may be associated with reduced developmental potential [48].…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have revealed species-dependent expression patterns of DNA methyltransferases (DNMTs) genes in mammalian oocytes and preimplantation embryos (Vassena et al 2005), and also an association between incomplete DNA methylation and the lack of NT success in mammals (Dean et al 2001;Bortvin et al 2003;Chung et al 2003). Severely reduced transcript levels of DNMT1 have been reported in cloned than in IVF or parthenote bovine embryos by Golding et al (2011).…”
Section: Discussionmentioning
confidence: 99%